AN INVESTIGATION OF PHYSICOCHEMICAL PARAMETERS OF GONGOLA RIVER CORRIDORS IN GOMBE STATE, NIGERIA - Adamu Garku, Nuru; Kotos A. Abubakar,; Ali, Ja’afaru; Isah , Zainab; Adamu Umar, Zaliha; Sa’idu, Haruna; Muhammad, Kabiru (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
The study investigated the physicochemical parameters of water from Gongola river corridors, Gombe State. In-situ measurements were conducted and the pH ranged between 6.27 ± 0.11 – 7.60 ± 0.02. The pH found in dry season is lower than the recommended limit indicating slightly acidic to a little bit above neutral condition of the river water. Contrarily, the range of Electrical conductivity (EC) (237.50±2.12 - 730.50±25.11µS/cm), Total dissolved solids (TDS) (111.75±1.76mg/L and 365.25±12.55 mg/L), Turbidity (3.25±0.83NTU to 13.39±2.82NTU), Biochemical Oxygen Demand (BOD) (1.91±0.33mg/L and 4.54±0.55 mg/L) and Chemical oxygen demand (COD) (1.91±0.33mg/L and 4.54±0.55 mg/L) found wet and dry season increased significantly in Almakashi and Gwani from the reference location. Furthermore, the range of the mean concentration of the chemical parameters of nitrate, phosphate, sulphate and chloride were 9.33 ± 2.46mg/L-1.18±1.25mg/L, 0.09±0.01 mg/L - 0.80±0.110 mg/L, 5.18 ±3 .16 mg/L-29.80 ± 13.22 mg/L and 37.70±8.45mg/L-168.72 ± 26.30mg/L respectively in which the highest values found in early wet season. The pH decreased from the reference river to the two sampling locations of Almakashi and Gwani rivers. All the chemical parameters examined in the Balanga dam (reference river) differed between the sampling locations (Almakashi and Gwani) compared to the reference river; though, it is within the recommended limit. There is need for regulation of activities that alters the physicochemical parameters of the water.